2009
DOI: 10.1016/j.jnoncrysol.2009.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of MoO3-containing zinc borophosphate glasses

Abstract: a b s t r a c tZnO-B 2 O 3 -P 2 O 5 glasses doped with MoO 3 were investigated in the series (100Àx)[0.5ZnO-0.1B 2 O 3 -0.4P 2 O 5 ]-xMoO 3 , where bulk glasses were obtained by slow cooling in air within the compositional region of 0 6 x 6 60 mol% MoO 3 . The incorporation of MoO 3 into the parent zinc borophosphate glass results in a weakening of bond strength in the structural network, which induces a decrease in chemical durability and glass transition temperature. Raman spectra reflect the incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This is similar to the structure found in sodium phosphomolybdates [14]. Simultaneously, with increasing MoO 3 content a band at 884 cm − 1 appears in the Raman spectra, which shows on the formation of Mo-O-Mo bridges between MoO 6 octahedra [6,14,25]. This band broadens and shifts to lower wavenumbers in glasses with more than 50 mol% MoO 3 , which can be caused by the formation of three-dimensional clusters composed of several MoO 6 octahedra interconnected by common edges.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is similar to the structure found in sodium phosphomolybdates [14]. Simultaneously, with increasing MoO 3 content a band at 884 cm − 1 appears in the Raman spectra, which shows on the formation of Mo-O-Mo bridges between MoO 6 octahedra [6,14,25]. This band broadens and shifts to lower wavenumbers in glasses with more than 50 mol% MoO 3 , which can be caused by the formation of three-dimensional clusters composed of several MoO 6 octahedra interconnected by common edges.…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion was made on the basis of the absence of Raman band at 884 cm − 1 (Fig. 7), ascribed to the vibrations of Mo-O-Mo bonds [6,14,25]. We suppose that the structure of this glass is built up of phosphate chains interconnected by bridging oxygens or by -O-Mo-Obridges of MoO 6 octahedra as well as in Mo 2 O 2 P 4 O 13 [32].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The spectra reveal different characteristic absorption bands corresponding to different vibration modes of phosphate and molybdate units. The bands in the region 1100-1250 cm −1 , 990-1050 cm −1 , 880-920 cm −1 and 680-740 cm −1 are assigned to the asymmetric stretching vibration of P O bond, asymmetric stretching vibration of P-O − mode, asymmetric stretching mode of P-O-P bond and symmetric stretching of P-O-P bond respectively [28][29][30][31]. The band observed around 750-840 cm −1 for glasses containing MoO 3 is assigned to the stretching vibration of MoO 4 2− anions [35].…”
Section: Tablementioning
confidence: 99%
“…A few studies of compositional dependence glass network structure in a few molybdophosphate glasses show that the increase of MoO 3 content leads to the transformation of Mo-O − and P O bonds into Mo-O-Mo and weaker Mo-O-P bridging bonds [28,29]. In zinc phosphate and borophosphate glasses [30,31] it has been observed that the incorporation of MoO 3 increases the depolymerization of phosphate chains and a gradual transformation of metaphosphate into diphosphate and orthophosphate units occurs. The Raman spectroscopic study of these glasses reveals that the ratio of MoO 6 /MoO 4 increases with increasing content of MoO 3 [32,33].…”
Section: Introductionmentioning
confidence: 99%